Not Just Arterial Damage: Increased Incidence of Venous Thromboembolic Events in Cardiovascular Patients With Elevated Plasma Levels of Apolipoprotein CIII. Issue 2 (22nd January 2019) - Olivieri, Oliviero; Turcato, Gianni; Moruzzi, Sara; Castagna, Annalisa; Girelli, Domenico; Pizzolo, Francesca; Friso, Simonetta; Sandri, Marco; Bassi, Antonella; Martinelli, Nicola
Abstract : Background: Apolipoprotein CIII (apo CIII) is a crucial player in triglyceride‐rich lipoprotein metabolism, but may also act pleiotropically, provoking inflammatory responses and stimulating coagulation. Elevated apoCIII plasma levels have been associated with increased activity of coagulation factors. Since these features of prothrombotic diathesis are linked with venous thromboembolism (VTE), we hypothesized that apo CIII plays a role in VTE. Methods and Results: We recorded nonfatal VTE events in 1020 patients (age 63.3±11.4 years; 29.1% women) with or without coronary artery disease (79.1% with coronary artery disease and 20.9% without coronary artery disease) during a long follow‐up. Complete plasma lipid and apolipoproteins were available for all patients. Forty‐five patients (4.4%) experienced nonfatal VTE events during a median follow‐up period of 144 months. Apo CIII plasma concentration at enrollment was higher in patients with VTE compared with patients without VTE (12.2 [95% CI, 11.10–13.5] mg/dL vs 10.6 [95% CI, 10.4–10.9] mg/dL, respectively; P =0.011). Patients with apo CIII levels above the median value (10.6 mg/dL) exhibited an increased risk of VTE (incidence rate, 6.0 [95% CI, 4.0–8.0] vs 1.8 [95% CI, 0.7–2.9] VTE events/1000 person‐years; unadjusted hazard ratio [HR], 3.42 [95% CI, 1.73–6.75]; P <0.001). This association was confirmed after adjustment for sex, age, coronary artery disease diagnosis, body mass index, hypertension, and anticoagulant treatment at enrollment (HR, 2.66; 95% CI, 1.31–5.37 [ P =0.007]), with inclusion of lipid parameters in the Cox model (HR, 3.74; 95% CI, 1.24–11.33 [ P =0.019]), and even with exclusion of patients who died at follow‐up (HR, 3.92; 95% CI, 1.68–9.14 [ P =0.002]) or patients taking anticoagulants (HR, 3.39; 95% CI, 1.72–6.69 [ P <0.001]). Conclusions: Our results suggest that high plasma apo CIII concentrations may predict an increased risk of VTE in patients with cardiovascular disease.